THE IMPACT OF ESG DISCLOSURE, GREEN ACCOUNTING, AND SUSTAINABILITY REPORTING ON FINANCIAL PERFORMANCE: (THE MODERATING ROLE OF FIRM SIZE) - Melina Apriliani; Dien Noviany Rahmatika; Eva Anggra Yunita (Politeknik Negeri Ambon, 2026)
Introduction: This research intends to investigate the effect of Environmental, Social, Governance (ESG), Green Accounting, and Sustainability Reporting on business financial performance, utilizing firm size as a moderating variable. Consumer products businesses listed on the Indonesia Stock Exchange (IDX) between 2021 and 2025 were the subject of this study. Methods: This research utilizes secondary data acquired from annual reports, financial reports, and sustainability reports of consumer goods businesses listed on the IDX for the 2021-2025 timeframe. The analytical approaches employed were multiple linear regression and moderated regression analysis (MRA).Methods: This research utilizes information obtained from secondary sources, including yearly reports, financial statements, and sustainability updates of consumer goods firms that are registered on the IDX from 2021 to 2025. The analytical approaches applied were multiple linear regression and moderated regression analysis (MRA).Results: The results indicate that ESG disclosure and sustainability reporting have a positive and significant effect on financial performance, while green accounting has no significant effect. In addition, firm size does not moderate the relationship between ESG disclosure, green accounting, sustainability reporting, and financial performance.Contribution: Using firm size as a moderating variable, this study examines the impact of sustainability reporting, green accounting, and environmental, social, and governance (ESG) disclosure on corporate financial performance. Consumer products businesses listed on the Indonesia Stock Exchange (IDX) between 2021 and 2025 were the subject of this study. It is envisaged that this study will cover a research gap, as previous studies on sustainability. Keywords: Company Financial Performance, Company Size, Environmental, Green Accounting, Social, Governance (ESG), Sustainability Reporting